Digital Media and Emotional Communication for Indonesian Migrant Workers (PMIs): A Uses and Gratifications Analysis - Eka. M. Taufani; Ardiyansyah; Muhammad Al Hafizh (INJECT (Interdisciplinary Journal of Communication), 2025)
Indonesian Migrant Workers (PMIs) face emotional challenges in maintaining family harmony due to geographical distance and dual roles. This study examines how PMIs use digital media to sustain emotional communication with their nuclear families, guided by the Uses and Gratifications Theory. Using a qualitative case study approach, data were collected through semi-structured interviews and digital communication documentation. Results show that digital platforms meet affective needs, maintain social bonds, and provide emotional relief. Gender influences the types of gratifications sought, while families emphasize reciprocal communication. Despite barriers such as time differences and limited access, video calls and messaging foster emotional closeness. Digital media play a vital role in supporting the emotional well-being of PMI and preserving long-distance family relationships.